(untitled) (Ustozlar uchun, 2025)
This thesis addresses the issues of developing an inventory and logistics management system for online retail stores. The need for effective systems to meet customer demands in the rapidly growing e-commerce sector is analyzed. The main tasks of inventory management and logistics, their integration, and the importance of effective management are discussed. Additionally, the potential to improve the efficiency of these systems through modern technologies such as cloud systems, artificial intelligence, IoT, and blockchain is demonstrated. The goal of the thesis is to ensure the application of innovative approaches and new technologies in the creation of systems for online retail stores. These new systems enable the automation of business processes, cost reduction, and the creation of opportunities for providing high-quality services to customers. Recommendations include the continuous update of technologies, optimization of logistics processes, and the provision of convenient delivery services to customers.